2015
DOI: 10.2460/ajvr.76.9.771
|View full text |Cite
|
Sign up to set email alerts
|

Effects of premedication with sustained-release buprenorphine hydrochloride and anesthetic induction with ketamine hydrochloride or propofol in combination with diazepam on intraocular pressure in healthy sheep

Abstract: Results suggested that both ketamine-diazepam and propofol-diazepam combinations were suitable for IOA without increasing IOP in sheep. The use of SRB should be avoided in sheep when increases in IOP are undesirable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…Methods of restraint should also be taken into consideration, as pressure applied on the jugular vein during capture and testing could influence the results . Intraocular pressure can be affected by sedation and general anesthesia as well as different types of tonometers used . The values of IOP obtained in the population of fallow deer were close to the values in the brown brocket deer (15.3 mm Hg) .…”
Section: Discussionsupporting
confidence: 82%
“…Methods of restraint should also be taken into consideration, as pressure applied on the jugular vein during capture and testing could influence the results . Intraocular pressure can be affected by sedation and general anesthesia as well as different types of tonometers used . The values of IOP obtained in the population of fallow deer were close to the values in the brown brocket deer (15.3 mm Hg) .…”
Section: Discussionsupporting
confidence: 82%
“…Recent studies in mice and rats demonstrated an analgesic effect of 48–72 hr duration following a single s.c. injection of different SR‐buprenorphine compounds (Carbone, Lindstrom, Diep, & Carbone, ; Chum et al., ; Clark, Clark, & Hoyt, ; Foley, Liang, & Crichlow, ; Healy et al., ; Jirkof, Tourvieille, Cinelli, & Arras, ; Kendall et al., ). Similar SR‐buprenorphine compounds have been used in dogs (Nunamaker et al., ; Tomas, Bledsoe, Wall, Davidson, & Lascelles, ), cats (Catbagan, Quimby, Mama, Rychel, & Mich, ; Enomoto et al., ; Johnson et al., ), rabbits (DiVincenti, Meirelles, & Westcott, ), Göttingen minipigs (Thiede et al., ), guinea pigs (Smith, Wegenast, Hansen, Hess, & Kendall, ), sheep (Gatson, Pablo, Plummer, & Granone, ; Walkowiak & Graham, ; Zullian et al., ), alpaca (Dooley et al., ), elephant seals (Molter et al., ), and macaques (Nunamaker et al., ). However, the SR‐buprenorphine formulations used in these studies were either unknown or compounded products and, in most of these studies, the authors reported skin lesions at the site of injections, ranging from simple s.c. nodules to abscesses, open wounds, and necrotic lesions likely caused by the viscosity of the product or the formulation matrix (Carbone et al., ; Catbagan et al., ; Clark et al., ; DiVincenti et al., ; Foley et al., ; Molter et al., ; Nunamaker et al., , ; Thiede et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…| 503 Tomas, Bledsoe, Wall, Davidson, & Lascelles, 2015), cats (Catbagan, Quimby, Mama, Rychel, & Mich, 2011;Enomoto et al, 2017;Johnson et al, 2017), rabbits (DiVincenti, Meirelles, & Westcott, 2016), Göttingen minipigs (Thiede et al, 2014), guinea pigs (Smith, Wegenast, Hansen, Hess, & Kendall, 2016), sheep (Gatson, Pablo, Plummer, & Granone, 2015;Walkowiak & Graham, 2015;Zullian et al, 2016), alpaca (Dooley et al, 2017), elephant seals (Molter et al, 2015), and macaques (Nunamaker et al, 2013).…”
mentioning
confidence: 99%
“…Human studies have reported both increases and decreases in IOP following ketamine injection alone, along with a dependence on dosage,1417 so there is some confusion in the literature as to the effects of ketamine on IOP. The most common animal models in which the effects of anesthesia on IOP have been studied are rodents, sheep, and NHPs; other studies have also included rabbits, cows, pigs, dogs, and cats 1822. Raposo et al reported the effect of four different anesthetics on capuchin monkeys, which included ketamine-xylazine and ketamine-dexmedetomidine 23.…”
mentioning
confidence: 99%